A Multiple-Baseline Evaluation of Acceptance and Commitment Therapy Focused on Repetitive Negative Thinking for Comorbid Generalized Anxiety Disorder and Depression - Ruiz, Francisco J.; Luciano, Carmen; Flórez, Cindy L.; Suárez-Falcón, Juan C.; Cardona-Betancourt, Verónica (Frontiers in Psychology, 2020)
Repetitive negative thinking (RNT) is a core feature of generalized anxiety disorder (GAD) and depression. Recently, some studies have shown promising results with brief protocols of acceptance and commitment therapy (ACT) focused on RNT in the treatment of emotional disorders in adults. The current study analyzes the effect of an individual, 3-session, RNT-focused ACT protocol in the treatment of severe and comorbid GAD and depression. Six adults meeting criteria for both disorders and showing severe symptoms of at least one of them participated in the study. A delayed multiple-baseline design was implemented. All participants completed a 5-week baseline without showing improvement trends in emotional symptoms (Depression Anxiety and Stress Scale – 21; DASS-21) and pathological worry (Penn State Worry Questionnaire; PSWQ). The ACT protocol was then implemented, and a 3-month follow-up was conducted. Five of the 6 participants showed clinically significant changes in the DASS-21 and the PSWQ. The standardized mean difference effect sizes for single-case experimental design were very large for emotional symptoms (d = 3.34), pathological worry (d = 4.52), experiential avoidance (d = 3.46), cognitive fusion (d = 3.90), repetitive thinking (d = 4.52), and valued living (d = 0.92 and d = 1.98). No adverse events were observed. Brief, RNT-focused ACT protocols for treating comorbid GAD and depression deserve further empirical tests.